Effectiveness of Triethanolamine as Emulsifier in Chamomile Lotion Stability - Asari, Yunita Dwi; Nur’ Aini, Laela; Ikmalanas, Salma; Paramita, Vita (Journal of Vocational Studies on Applied Research, 2024)
Lotion is a cosmetic product with a lighter consistency than cream, consisting of a mixture of oil phase and water phase, with emulsifying ingredients, moisturizers, active substances, and fragrances. Its function is to hydrate the skin, reduce irritation, and protect from environmental influences. Chamomile extract and niacinamide provide additional benefits, such as anti-inflammatory characteristics and increased skin moisture. This study aims to evaluate the effectiveness of triethanolamine (TEA) as an emulsifier in lotion stability during storage, as well as the effect of stirring temperature on lotion quality. The research method used a 2 x 3 factorial design quantitatively. Of the 8 lotion formulas tested, only formula 3 met the standard requirements of organoleptically, pH, specific gravity and homogeneity tests. This formula has a TEA volume of 2 ml, mixing time for 25 minutes at 70℃, pH 8, foam texture, slightly yellow-green color, specific gravity 0.972, and homogeneity. This formula provides a moisturizing effect on the skin without side effects